ANALISIS NILAI TAMBAH PENGOLAHAN KEDELAI MENJADI SUSU KEDELAI PADA INDUSTRI RUMAH TANGGA SARI KEDELAI “BU ADE” DI CATURTUNGGAL KEC. DEPOK KABUPATEN SLEMAN DIY - Yuliyanto, Dwi; Widiatmi, Susi; Mawardi, Nanang Kusuma (JURNAL ILMIAH AGRITAS, 2023)
This study aims to determine the process of processing soy into soy milk and to find out the added value that exists in the Household Industry of Soy Essence "Bu Ade". This research was carried out in the Household Industry of Soybean Essence "Bu Ade". This research was conducted using descriptive analytical and quantitative methods (Hayami method). The hypothesis test used is a statistical test (T-test). From the results of the study, it shows that the soy milk product produced by soy juice is "Bu Ade" it has a value added of 71% for 2017; 71% for 2018; 90% for 2019; 95% for 2020; and 94% for 2021. The added value of soy milk in the household industry of soy juice "Bu Ade" according to the Hayami method rules if it has an added value ratio of more than 40% is said to be high. So it can be concluded that the soy milk products produced by the household industry of Soy Juice "Bu Ade" have a high added value.